Penerapan Expressive Writing Therapy pada Pasien dengan Gangguan Persepsi Sensori: Halusinasi Pendengaran di Panti ODGJ Palembang - Clarita Lefinda Morin Nahak; Aprida Manurung; Bangun Dwi Hardika (Lembaga Pengembangan Kinerja Dosen, 2026)
Schizophrenia is a severe, chronic mental disorder often characterized by auditory hallucinations, which can trigger maladaptive responses such as violent behavior, social isolation, and even suicide risk. Therefore, non-pharmacological complementary therapies are needed to help patients manage their symptoms independently, one of which is expressive writing therapy. This case study aims to describe nursing care and determine the effect of expressive writing therapy on reducing the signs and symptoms of auditory hallucinations in patients at a Palembang Mental Health Center. The research design used was a descriptive case study with a one-group pretest and posttest approach on six respondents with sensory perception disorders: auditory hallucinations. Data were collected through interviews, observations, and the Psychotic Symptom Rating Scale (PSYRAT) instrument, with the intervention given for three consecutive days, each 15 minutes per session. The results showed that all six respondents experienced a decrease in PSYRAT scores after the intervention, from the severe to very severe category at the initial assessment to the moderate category at the final evaluation, indicating that this therapy helped shift the patient's focus from internal stimuli, making the patient more cooperative and gradually reducing the intensity of their hallucinatory symptoms. Expressive writing therapy is considered effective in reducing the signs and symptoms of auditory hallucinations and can be used as an independent psychiatric nursing intervention that can be integrated into daily rehabilitation programs.